Does It Matter if You Are Observed by Others? Evidence from Donations in the Field*. (18th January 2013) - Alpízar, Francisco; Martinsson, Peter
Abstract We investigate whether people's donations in the field are affected by the presence of others. In the analysis, we distinguish between individuals who arrived at a national park alone and those who arrived as members of a group. We also investigated the effect of donations being made in the presence of a third party made in the presence of a third party. We find that donations are significantly more frequent for individuals who are members of a group. When a third party is present, we find that the total donations by individuals who are a part of a group are significantly higher than those of lone travelers, mainly because of the increased probability of donating.